Species diversity and phylogenetic relationships of snapper (Lutjanidae: Lutjanus) inferred from mitochondrial DNA markers - Hai Yen, Dinh Thi; Ngoc Lam, Hoang; Thi Ha, Vo; Thi Oanh, Truong; Quang Sang, Tran; Thuy Binh, Dang (Vietnam Journal of Biotechnology, 2023)
Snappers (Lutjaniformes: Lutjanidae) are commercially important fishes in tropical and subtropical waters. However, species complexes still exist due to low-level morphological differences. Additionally, current availability of molecular sequences has led to significant changes in fish taxonomy. Therefore, species diversity of lutjanids is still unclear. In this study, we applied two mitochondrial markers (16S rRNA and Cytochrome c oxidase subunit I, COI mtDNA) to investigate species diversity and phylogenetic relationships of lutjanid species collected from the coastal waters of Nghe An – Ha Tinh provinces, Northern Central, Vietnam. A total of 17 Lutjanus species have been identified using morphological and molecular methods. Combined with Genbank sequences, the phylogenetic tree was constructed using Neighbor Joining and Maximum Likelihood approaches based on 16S rRNA and COI mtDNA data set. Two main lineages have been detected with inconsistent basal clades between two topologies. Members of species complexes also showed a certain degree of closely relationships; however, conflicts between two topologies have also been recorded. These data contribute to the assessment of lutjanid biodiversity in Vietnam, and for resource management and conservation.